2017
DOI: 10.1002/pc.24511
|View full text |Cite
|
Sign up to set email alerts
|

Sisal fiber‐reinforced green composites: Effect of ecofriendly fiber treatment

Abstract: This research endeavor explores the effect of economical and environment‐friendly treatment of sisal fibers, prior to their incorporation into poly‐lactic acid (PLA). Biocomposites incorporating sisal fibers (30% [w:w]) treated with sodium bicarbonate (10% [w:v]) aqueous solution for varying time periods (24, 72, 120, and 168 h) were developed using extrusion‐injection molding process. Thermogravimetric analysis, morphological examination, Fourier‐transform infrared spectroscopy, and lignocellulosic compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…This result indicates that composites reinforced with untreated Jute fibers (i.e., Jute-AR) are characterized by better fiber-matrix interfacial adhesion than surface treated ones (i.e., Jute-T) [47]. Due to the soaking of jute fibers in the NaHCO 3 solution, a reduction of lignin and hemicellulose components from the fiber bulk occurred [44], thus favoring the triggering of damage phenomena at the interface.…”
Section: Effect Of Treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…This result indicates that composites reinforced with untreated Jute fibers (i.e., Jute-AR) are characterized by better fiber-matrix interfacial adhesion than surface treated ones (i.e., Jute-T) [47]. Due to the soaking of jute fibers in the NaHCO 3 solution, a reduction of lignin and hemicellulose components from the fiber bulk occurred [44], thus favoring the triggering of damage phenomena at the interface.…”
Section: Effect Of Treatmentmentioning
confidence: 94%
“…To overcome this problem, an eco-friendly and cost-effective treatment consisting of the immersion of natural fibers in sodium bicarbonate solution was investigated in the last years by several researchers [32,[43][44][45][46][47][48][49]. In particular, they showed that the interaction between the mildly alkaline solution and the fiber surface is considered similar to that of traditional alkalization treatment [43].…”
Section: Introductionmentioning
confidence: 99%
“…An improvement in mechanical and thermal properties of hemp/polyester composites was found by sodium bicarbonate treatment . Chaitanya and Singh reported that mechanical and thermal properties were enhanced of sisal/polylactic acid (PLA) composites by sodium bicarbonate treatment and also concluded that sodium bicarbonate treatment has potential to replace NaOH treatment. A similar type of study was performed by Fiore et al in which mechanical properties of sisal/epoxy composites were enhanced by this eco‐friendly treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This sector is more and more interested in plant fibers in order to use renewable and perennial materials or in secondary structures in applications that respond to the concern for the preservation of the environment. [11][12][13][14][15][16][17][18][19][20][21][22]. All natural fibers are composed of Cellulose, hemicelluloses and Lignin, these elements have an impact on the mechanical propertiess [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%